Profile of poisoning admissions in Malaysia - Rajasuriar, R.; Awang, R.; Hashim, S.B.H.; Rahmat, H.R.B.H. (2007)
We retrospectively reviewed poisoning admissions to all government health facilities from 1999 to 2001, in an effort to expand our current knowledge on poisoning in Malaysia to a level that better reflects a nationwide burden. There were 21 714 admissions reported with 779 deaths. The case-fatality rate was 35.88/1000 admissions. The majority of admissions (89.7%) and deaths (98.9%) occurred in adults. Some 55.1% of all admissions were female, mostly involving pharmaceutical agents. Male poisoning admissions were more often due to chemical substances. The prevalence of poisoning and death was highest among Indians compared to all other races in Malaysia. Overall, the majority of poisoning admissions were due to pharmaceutical agents, with agents classified as non-opioid analgesics, anti-pyretics and anti-rheumatics the most common. Pesticides accounted for the largest number of fatalities. It was also the commonest substance reported in cases of intentional self-harm. Most cases of poisoning admissions occurred due to accidental exposure (47%), followed by cases of intentional self-harm (20.7%). Overall, this study has managed to contribute substantial additional information regarding the epidemiology of poisoning in Malaysia, highlighting important issues, such as the rampant poisonings involving pesticides and analgesics, as well as the high prevalence of poisoning among Indians in Malaysia.